Real-time micro-doppler radar signal processing - Gong, Wei (Nanyang Technological University, 2020)
With the rapid development of technology, the new high technology has played an important role in human life and also has greatly changed people's lifestyles. The high technology had been applied to many applications to improve people’s life. Building security, smart home and street lighting, to achieve this purpose, radar will be the best choice and it will instead of camera, ultrasonic sensors and Pyro-electric Infrared Detector. In order to use radar more widely, high recognition and classification rate will become more important when applied radar. This project is aimed to study real time data processing and how to improve the recognition accuracy. The report will provide literate reviews, including some basic radar principles and data processing procedures. In addition, it also introduces how to implement the hardware and software to analyze the radar signals. We could judge the measurement accuracy of different situations by analyzing the result and we can make more effective to use the radar.